Fiscal Policy Measures of Air Protection: Ukrainian Realities and the EU Experience - Kurylo, Volodymyr; Duliba, Yevheniia; Kurylo, Inna; Mushenok, Viktor (European Journal of Sustainable Development, 2020)
Nowadays environmental protection and the rational use of natural resources have become priorities of the state-building strategy in almost all developed countries of the world. Effective financing of these activities is required for the development and adoption of national targeted, local programs for environmental protection, for the sustainable development of society, for the rational use and reproduction of natural resources. The article is devoted to the research of the current tendencies of the use of fiscal policy measures in the implementation of the national environmental policy in the sphere of atmospheric air protection in Ukraine. The ways of improvement of environmental taxation and development of the main ways of development and expansion of the system of ecological taxation and ecological governance in Ukraine were discovered. Keywords: atmospheric air, environmental air safety, fiscal policy, environmental taxation, implementation of the national environmental policy,